2009
DOI: 10.1038/jhg.2009.63
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the IL1RAPL1 gene into the duplication junction of the dystrophin gene

Abstract: Duplications of one or more exons of the dystrophin gene are the second most common mutation in dystrophinopathies. Even though duplications are suggested to occur with greater complexity than thought earlier, they have been considered an intragenic event. Here, we report the insertion of a part of the IL1RAPL1 (interleukin-1 receptor accessory protein-like 1) gene into the duplication junction site. When the actual exon junction was examined in 15 duplication mutations in the dystrophin gene by analyzing dyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…18,19 The suggested minimum requirement for favorable homologous recombination is 75% of identity between Alu elements. 20,21 In our study, we hypothesize that the de novo deletion of 10895 bp in SPTBN2 gene was generated by an unequal homologous recombination event, due to a misalignment between Alu Sx in intron 12 (5ʹ deletion boundary) of SPTBN2 gene and Alu Sx in intron 20 (3ʹ deletion boundary). Both Alu Sx show 86% sequence identity (91% without gaps) and a microhomology domain of 50 bp.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…18,19 The suggested minimum requirement for favorable homologous recombination is 75% of identity between Alu elements. 20,21 In our study, we hypothesize that the de novo deletion of 10895 bp in SPTBN2 gene was generated by an unequal homologous recombination event, due to a misalignment between Alu Sx in intron 12 (5ʹ deletion boundary) of SPTBN2 gene and Alu Sx in intron 20 (3ʹ deletion boundary). Both Alu Sx show 86% sequence identity (91% without gaps) and a microhomology domain of 50 bp.…”
Section: Discussionmentioning
confidence: 85%
“…These sequences of about 300 base pairs share a great level of identity and allow more efficient homologous recombination than sequences with an imperfect identity which would represent an inefficient target 18,19 . The suggested minimum requirement for favorable homologous recombination is 75% of identity between Alu elements 20,21 . In our study, we hypothesize that the de novo deletion of 10895 bp in SPTBN2 gene was generated by an unequal homologous recombination event, due to a misalignment between Alu Sx in intron 12 (5ʹ deletion boundary) of SPTBN2 gene and Alu Sx in intron 20 (3ʹ deletion boundary).…”
Section: Discussionmentioning
confidence: 99%
“…The 2 male patients of this family presenting with the same isolated intragenic IL1RAPL1 duplication (III.1and III.5) share a similar phenotype, including autism spectrum disorders, short attention span, and dyspraxia without ID as well as dysmorphic features. Froyen et al [2007] and Zhang et al [2009] both reported a case of IL1RAPL1 duplication associated with ID, but in both cases, the CNV encompassed other XLID genes such as CASK and DMD. Four patients in the DECIPHER database (274669, 277292, 249698 and 280583; https://decipher.sanger.ac.uk/) harbour an overlapping intragenic IL1RAPL1 duplication.…”
Section: Discussionmentioning
confidence: 99%
“…(1), is associated with a non-syndromic form of mental retardation (MR). Similar to some other genes involved in cognitive impairment (24), IL1RAPL1 mutations are associated with a spectrum of cognitive impairments ranging from MR to autism (511). …”
Section: Introductionmentioning
confidence: 98%